Hydrogen Dynamics in Trichodesmium Colonies and Their Potential Role in Mineral Iron Acquisition - Eichner, Meri; Basu, Subhajit; Gledhill, Martha; de Beer, Dirk; Shaked, Yeala (Frontiers in Microbiology, 2019)
N2-fixing cyanobacteria mediate H2 fluxes through the opposing processes of H2 evolution, which is a by-product of the N2 fixation reaction, and H2 uptake, which is driven by uptake hydrogenases. Here, we used microelectrodes to characterize H2 and O2 dynamics in single natural colonies of the globally important N2 fixer Trichodesmium collected from the Gulf of Eilat. We observed gradually changing H2 dynamics over the course of the day, including both net H2 evolution and net H2 uptake, as well as large differences in H2 fluxes between individual colonies. Net H2 uptake was observed in colonies amended with H2 in both light and dark. Net H2 evolution was recorded in the light only, reflecting light-dependent N2 fixation coupled to H2 evolution. Both net H2 evolution and H2 uptake rates were higher before 2 pm than later in the day. These pronounced H2 dynamics in the morning coincided with strong net O2 uptake and the previously reported diel peak in N2 fixation. Later in the afternoon, when photosynthesis rates determined by O2 measurements were highest, and N2 fixation rates decrease according to previous studies, the H2 dynamics were also less pronounced. Thus, the observed diel variations in H2 dynamics reflect diel changes in the rates of O2 consumption and N2 fixation. Remarkably, the presence of H2 strongly stimulated the uptake of mineral iron by natural colonies. The magnitude of this effect was dependent on the time of day, with the strongest response in incubations that started before 2 pm, i.e. the period that covered the time of highest uptake hydrogenase activity. Based on these findings, we propose that by providing an electron source for mineral iron reduction in N2-fixing cells, H2 may contribute to iron uptake in Trichodesmium colonies.